Chimeric peptide-mediated siRNA transduction to inhibit HIV-1 infection. (21st April 2017) - Bivalkar-Mehla, Shalmali; Mehla, Rajeev; Chauhan, Ashok
Abstract: Persistent human immunodeficiency virus 1 (HIV-1) infection provokes immune activation and depletes CD4 + lymphocytes, leading to acquired immunodeficiency syndrome. Uninterrupted administration of combination antiretroviral therapy (cART) in HIV-infected patients suppresses viral replication to below the detectable level and partially restores the immune system. However, cART-unresponsive residual HIV-1 infection and elusive transcriptionally silent but reactivatable viral reservoirs maintain a permanent viral DNA blue print. The virus rebounds within a few weeks after interruption of suppressive therapy. Adjunct gene therapy to control viral replication by ribonucleic acid interference (RNAi) is a post-transcriptional gene silencing strategy that could suppress residual HIV-1 burden and overcome viral resistance. Small interfering ribonucleic acids (siRNAs) are efficient transcriptional inhibitors, but need delivery systems to reach inside target cells. We investigated the potential of chimeric peptide (FP-PTD) to deliver specific siRNAs to HIV-1-susceptible and permissive cells. Chimeric FP-PTD peptide was designed with an RNA binding domain (PTD) to bind siRNA and a cell fusion peptide domain (FP) to enter cells. FP-PTD-siRNA complex entered and inhibited HIV-1 replication in susceptible cells, and could be a candidate for in vivo testing.